PENGARUH LITERASI KEUANGAN SYARIAH KEPERCAYAAN DAN KUALITAS PELAYANAN TERHADAP MINAT MENABUNG SANTRI DI KOPERASI PESANTREN AL UTSMANI BEDDIAN - Siti Habibatur Rahma Rahma; Siti Masita (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2026)
The development of Islamic finance in Indonesia highlights the importance of Islamic financial literacy, trust, and service quality in shaping financial behavior, including among students in Islamic boarding schools. This study aims to analyze the effect of Islamic financial literacy, trust, and service quality on students’ saving intention at the Al-Utsmani Beddian Islamic Boarding School Cooperative. This research employed a quantitative approach using a survey method. The sample consisted of 110 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that Islamic financial literacy, trust, and service quality partially have a positive and significant effect on students’ saving intention. Simultaneously, the three variables significantly influence saving intention. This study implies that improving Islamic financial education, strengthening trust, and enhancing service quality are important factors in developing Sharia-based Islamic boarding school cooperatives.